2023
DOI: 10.1002/fsn3.3411
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and opportunities related to the use of bee products in food processing

Abstract: One of the oldest examples of the existence of beekeeping is the murals from the Araña Cave in Spain, which show people collecting honey from the nest of untamed bees. In ancient times, honey was used as a medicine and also to embalm corpses. During Greek feasts, it was an indispensable part of the menu. However, the greatest boom in beekeeping took place in ancient Rome, where hives made of straw and clay were found, dating back to 900 B.C. (Kritsky, 2017). The Egyptians placed a vessel filled with a "golden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 217 publications
0
6
0
Order By: Relevance
“…The BP fermentation in the BB formation process changed the bioactive compounds’ amounts and chemical profiles to increase their bioavailability and bioaccessibility [ 83 , 84 , 85 ]. Also, lactic fermentation by bacteria and/or yeast degrades the pollen wall and releases PCs, which are associated with carbohydrates or proteins [ 84 , 86 ]. Additionally, Zhang et al [ 87 ] reported that the contents of flavonoids in fermented BP increased up to 144.66-fold/units, and of phenolic acids only up to 28.9-fold compared to unfermented BP.…”
Section: Resultsmentioning
confidence: 99%
“…The BP fermentation in the BB formation process changed the bioactive compounds’ amounts and chemical profiles to increase their bioavailability and bioaccessibility [ 83 , 84 , 85 ]. Also, lactic fermentation by bacteria and/or yeast degrades the pollen wall and releases PCs, which are associated with carbohydrates or proteins [ 84 , 86 ]. Additionally, Zhang et al [ 87 ] reported that the contents of flavonoids in fermented BP increased up to 144.66-fold/units, and of phenolic acids only up to 28.9-fold compared to unfermented BP.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, various studies have been conducted to assess the incorporation of bee pollen into yogurt formulation and evaluate the composition; physicochemical, sensory, microbial, and rheological properties; antioxidant capacity, microstructure, amino acids, and probiotic growth and viability [10][11][12]. As mentioned above, BP provides important nutrients and bioactive compounds with positive impact on human health; moreover, often it is recognized as complete food [13]. Thus, the study of BP incorporating into yogurt is valuable for industrial applications.…”
Section: Research Articlementioning
confidence: 99%
“…Several studies demonstrate that bee products exhibit antibacterial, [3] antifungal, [4] antiviral, [5] antiprotozoal, [6] anticancer, [7] features thanks to bioactive compounds they contain [8] . Apitherapy is a significant type of complementary treatment using bee products for both the cure and prevention of various diseases involving diabetic foot ulcers, injuries, rhinitis and rheumatoid arthritis since ancient times [9,10] …”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, it is a mixture of fermented bee pollen, honey and the digestive enzymes of bee, and is a rich food in terms of carbohydrates, proteins, fats, as well as vitamins, and minerals [12] . Besides, bee bread is an essential food for queen bee and baby bees in the hive, so it is called the food of baby bee [9] . Moreover, in addition to providing micro and macronutrients for bee colonies, it is a primary source to obtain royal jelly which is another precious bee product used to feed queen bees [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation